The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1080/07420528.2019.1689398
|View full text |Cite
|
Sign up to set email alerts
|

The association between sleep chronotype and obesity among black and white participants of the Bogalusa Heart Study

Abstract: Research indicates that sleep duration and quality are inter-related factors that contribute to obesity, but few studies have focused on sleep chronotype, representing an individual's circadian proclivity, nor assessed these factors in racially diverse middle-aged samples. We examined the associations between chronotype and obesity among black and white men and women participating in the Bogalusa Heart Study (BHS).Body mass index (BMI) and sleep data were available for 1,197 middle-aged men and women (mean age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 80 publications
1
20
3
Order By: Relevance
“…These findings are supported by strong evidence from observational studies on the associations between evening chronotype and higher risks for metabolic diseases ( Merikanto et al, 2013 ; Yu et al, 2015 ; Knutson and von Schantz, 2018 ). Furthermore, some studies have found associations between a higher body mass index or obesity and chronotype ( Celis-Morales et al, 2017 ; de Punder et al, 2019 ; Sun et al, 2020 ), but these associations have not been confirmed among our study population ( Maukonen et al, 2019 ). Future studies should examine in more detail the metabolic aspect of the association between NR1D2 gene and chronotype.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These findings are supported by strong evidence from observational studies on the associations between evening chronotype and higher risks for metabolic diseases ( Merikanto et al, 2013 ; Yu et al, 2015 ; Knutson and von Schantz, 2018 ). Furthermore, some studies have found associations between a higher body mass index or obesity and chronotype ( Celis-Morales et al, 2017 ; de Punder et al, 2019 ; Sun et al, 2020 ), but these associations have not been confirmed among our study population ( Maukonen et al, 2019 ). Future studies should examine in more detail the metabolic aspect of the association between NR1D2 gene and chronotype.…”
Section: Discussioncontrasting
confidence: 75%
“…These findings are supported by strong evidence from observational studies on the associations between evening chronotype and higher risks for metabolic diseases (Merikanto et al, 2013;Yu et al, 2015;Knutson and von Schantz, 2018). Furthermore, some studies have found associations between a higher body mass index or obesity and chronotype (Celis-Morales et al, 2017;de Punder et al, 2019;Sun Adjusted for age, sex, 5 principal components, and genotyping batch. Decreasing beta and increasing odds ratios refer to evening type.…”
Section: Discussionmentioning
confidence: 62%
“…Low adherence to a healthy nutritional pattern such as Mediterranean diet represents an additional risk for the development of obesity [ 55 ]. As well-known obesity is currently considered a known risk factor for cancer [ 56 , 57 ], and at the same time it is often detected in subjects with the evening chronotype [ 58 , 59 ]. This association could explain the increased risk of developing obesity–related cancers, such as prostate and breast cancer in the evening chronotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2] Also, observational studies show associations between being an evening person and risk for diabetes, [9] metabolic syndrome, [9] sarcopenia [9] and obesity. [10] Further, Mendelian randomisation analyses indicate that being a morning person may lead to better mental health. [2] Recent studies have shown that brain structure as determined by neuroimaging methods is highly heritable, [11,12] and the growing use of imaging techniques in genetic studies has opened up new lines of investigation for several phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Also, observational studies show associations between being an evening person and risk for diabetes,[9] metabolic syndrome,[9] sarcopenia[9] and obesity. [10] Further, Mendelian randomisation analyses indicate that being a morning person may lead to better mental health. [2]…”
Section: Introductionmentioning
confidence: 99%